Pemikiran Murtadha Muthahhari Tentang Kesetaraan Perempuan - M Aziz Mukti (Program Studi Pendidikan Agama Islam, 2021)
Murtadha Motahhari is a prominent figure in Iran. He was born on February 2, 1920. He is the son of a prominent Iranian cleric, Muhammad Husein Mutahhari. Murtadha loves kalam and philosophy. While in Qum, Murtadha met Imam Khomeini and studied with him on ethics and philosophy. In 1950, Murtadha moved from Qum to Tehran. He began teaching philosophy at the University of Tehran. Murtadha became a great thought figure for Iran. One of her most important thoughts is about women's equality against the western version of equality. Murtadha explains that the west is late and hasty regarding equality. Western equality also leads to uniformity. Islam has judged that men and women are both human beings who have differences from nature and innate. It is this difference that produces the beauty and happiness between the two.